2019
DOI: 10.7150/jca.32859
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pathological T3a upstaging on oncological outcomes of clinical T1 renal cell carcinoma: a meta-analysis

Abstract: Objective: The study aims to assess the prognostic impact of pathological T3a upstaging in clinical T1 renal cell carcinoma (RCC) on clinical outcomes.Methods: We performed a systematic literature search of PMC, Embase, Web of Science, and Cochrane library from inception to April 2019 for studies that investigated the prognostic significance of pathological T3a upstaging in clinical T1 RCC after surgery and conducted a standard meta-analysis on survival outcomes.Results: Overall, nine studies including 101,505… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…7 Previous studies have reported that patients with upstaged pT3 RCCa from cT1 have a poorer prognosis than those without. [8][9][10] However, previous reports on the oncological consequences of partial nephrectomy (PNx) and RNx in these patients are still conflicting. [11][12][13][14][15][16][17][18][19][20][21][22] In particular, when tumors are small but cT3 cannot be excluded from preoperative imaging studies, it is very troublesome to select PNx, although it is technically feasible.…”
Section: Introductionmentioning
confidence: 99%
“…7 Previous studies have reported that patients with upstaged pT3 RCCa from cT1 have a poorer prognosis than those without. [8][9][10] However, previous reports on the oncological consequences of partial nephrectomy (PNx) and RNx in these patients are still conflicting. [11][12][13][14][15][16][17][18][19][20][21][22] In particular, when tumors are small but cT3 cannot be excluded from preoperative imaging studies, it is very troublesome to select PNx, although it is technically feasible.…”
Section: Introductionmentioning
confidence: 99%
“…The role of PN in the treatment of cT1 RCC has been well studied. While Chen et al showed that the rate of cT1 upstaged to pT3a ranged from 3.2-31%, median 5.5% [3]. Moreover, upstaged cT1/pT3a RCC was associated with poor recurrence-free survival, overall survival, and cancer-speci c survival in the most of the reports [3].…”
Section: Discussionmentioning
confidence: 99%
“…While Chen et al showed that the rate of cT1 upstaged to pT3a ranged from 3.2-31%, median 5.5% [3]. Moreover, upstaged cT1/pT3a RCC was associated with poor recurrence-free survival, overall survival, and cancer-speci c survival in the most of the reports [3]. It has been showed that several factors would affect the prognostic of pT3a RCC, such as tumor size, invasion site, tumor grade and pathology type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations